2009
DOI: 10.1002/elan.200804421
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of PTH‐Cysteine by Adsorptive Stripping Square‐Wave Voltammetry

Abstract: The aim of this work is the study of cysteine by its derivative form. Cysteine derivation is done by Edman degradation and we obtain the phenylthiohydantoin of cysteine. Edman degradation is one of the most usual procedures for sequentate proteins. From this reaction, the phenylthiohydantoin amino acid derivative (PTH-amino acid) from the N-terminal one is obtained, leaving the new amino terminus for the next degradation cycle. To identify the produced PTH-derivative, a square-wave cathodic stripping voltammet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…). Among them, PTH cysteine exhibited a unique property that was not detected at 269 nm, which was reported previously . Therefore, the third residue in the PSA‐ C κ fusion protein was determined to be cysteine.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…). Among them, PTH cysteine exhibited a unique property that was not detected at 269 nm, which was reported previously . Therefore, the third residue in the PSA‐ C κ fusion protein was determined to be cysteine.…”
Section: Resultsmentioning
confidence: 67%
“…Therefore, the third residue in the PSA‐ C κ fusion protein was determined to be cysteine. In Edman cycles, a carry‐over (sequence lag) effect could occur in which the signal from a previous PTH amino acid is transferred to a subsequent cycle due to incomplete coupling and cleavage of the N‐terminal residue. In this study, peaks indicating glutamic acid (E) were observed at the third and fifth residue positions of the recombinant PSA‐ C κ fusion protein; these were considered as carry‐over.…”
Section: Resultsmentioning
confidence: 99%